A Triple Threat: Parents in Recovery During COVID-19. Issue 6 (November 2021) - Clark, Maria Carolina; Buswell, Jessica; Gold, Claudia; Peacock-Chambers, Elizabeth
Abstract : N/A: In this commentary, we describe the triple threat that parents in recovery face during the COVID-19 pandemic due to the loss of social support. We explore how the absence of human connection during the pandemic can be detrimental to parents in recovery as well as the parent-child relationship. We conclude by proposing strategies to offer critical support for families as this period of social isolation extends and the effects become increasingly apparent.